Effects of Med Fai 62 Brown Rice Flour and Protein Sources on The Quality of Dried Instant Noodles - Chooklin, Supasit; Srionnual, Sirinat; Thorasin, Thanikan; Thongnok, Sutasinee (Srinakharinwirot University Journal of Sciences and Technology, 2025)
This study investigated the optimal amount of brown rice flour from the Med Fai 62 variety by comparing the physical, chemical, and sensory properties, as well as consumer acceptance, of instant noodle products enriched with different protein sources. The results showed that the physical and chemical characteristics of instant noodles in which wheat flour was partially replaced by Med Fai 62 brown rice flour differed significantly from the control sample. Increasing the proportion of Med Fai 62 brown rice flour (10–30%) affected the lightness (L*), red-green (a*), and yellow-blue (b*) color values. Higher levels of brown rice flour resulted in a darker noodle color. The color values (L*, a*, and b*) ranged between 17.92–69.73, 3.35–11.00, and 6.10–29.88, respectively. As the proportion of brown rice flour increased, the L* and b* values decreased, while the a* values increased. Compared to commercial samples, the moisture content, water activity, and texture firmness of the instant noodles ranged between 0.39–12.95%, 0.13–0.61, and 0.38–29.73 N, respectively. Cooking time, cooking loss and water absorption ranged from 3.00–7.17 minutes, 1.68–7.13 times, and 25.32–31.65 grams, respectively. In terms of sensory quality, the instant noodles containing 10% Med Fai 62 brown rice flour received the highest overall liking score (8.23), which was not significantly different from the commercial instant noodle sample. The instant noodles with a 0.29% reduction in sodium chloride also received the highest overall liking score of 8.00. When comparing chemical properties and texture of the brown rice noodles enriched with protein, the moisture content, water activity, and firmness ranged from 5.28–8.04%, 0.58–0.66, and 14.50–17.48 N, respectively. These noodles exhibited increased cooking time and weight loss compared to the control. Sensory evaluation revealed that instant noodles with 10% Med Fai 62 brown rice flour enriched with soy protein powder received the highest overall liking score (7.87), while those enriched with cricket powder were not significantly different from the control. Therefore, dried instant noodles fortified with 10% Med Fai 62 brown rice flour, reduced sodium chloride by 0.29%, and enriched with soy protein or cricket powder have potential to a commercial product health-conscious consumer.